Minimize renewable distributed generator costs while achieving high levels of system uniformity and voltage regulation - Thai Dinh Pham; Le Chi Kien; Thang Trung Nguyen (Ain Shams Engineering Journal, 2024)
This research facilitates the placement of solar and wind-powered distributed generators (RDGs) in an unbalanced 3-phase IEEE 25-node distribution system intended to minimize the total expense of buying electricity from the grid and releasing carbon dioxide over twenty years. The probability distribution functions of Beta and Rayleigh are employed to attain solar illumination and wind velocity in a particular region. Unbalanced voltage deviation (UVD) and harmonic flows (HFs) from non-ideal loads and RDGs are considered. Metaheuristic methods are coded in MATLAB to find RDGs' location and capacity, and then OpenDSS is used to calculate power and harmonic issues. As a result, the total expenses can be reduced to $1.4141 million, which is 10.7% of the base system’s. Additionally, HFs and UVDs at every node follow the IEEE Std. 519 and the IEEE Std. 45-2002, respectively. So, the placement of RDGs has a beneficial position in unbalanced distribution systems.